FIGURE 8 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 8. Measurements of Mesosaccella rogovi sp. nov. (in mm). (A) Height to length. (B) Width to length. (C) Width to height. (D) Posterior length to length. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 20, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112